Everyone’s responsibility: Community partnerships and shared commitment for mental health promotion - Jung, Hyejin; Aguilar, Jemel P. (Social Work in Mental Health, 2016)
In this article, we use qualitative methods to understand the ways in which community involvement in a community-based mental health promotion conference encourages mental health care in an African-American community. We collected data through key informant interviews, focus groups, and participant observations at conference planning meetings and conferences, as well as archival documents related to the conference. We identify community partnerships and shared commitment as drivers of the outreach to people in the community, creators of a culturally relevant and supportive environment for mental health education, and, consequently, promoters of mental health care in the African-American community.
_eprint: https://doi.org/10.1080/15332985.2015.1130009
Keywords: African Americans; case studies; community partnerships; community-based programs; dept.swk; mental health and illness; mental health promotion